Instrumen Penilaian Autentik pada Pembelajaran Bahasa Arab di Madrasah Aliyah - Alfinnas, Haflah; Ali, Moh.; Syathori, A. (Study Program of Arabic Language Teaching, 2026)
This study aims to develop authentic assessment instruments for Arabic language learning at Madrasah Aliyah through a qualitative library research approach. The data in this study comprise primary and secondary sources, including textbooks, national and international scientific journals, previous research findings, and theoretical references on authentic assessment and Arabic language teaching. Data were collected through systematic documentation techniques, including searches of credible academic databases, library catalogs, and electronic journal repositories using relevant keywords. The subject of this study is the conceptual framework for the development of an authentic assessment instrument for four Arabic language skills. Data were analyzed using a descriptive-analytical content analysis, with data reduction, categorization, comparative analysis, and synthesis, and source triangulation to ensure the validity and credibility of the findings. The results indicate that authentic assessment instruments for Arabic language learning are characterized by four main dimensions: task authenticity, cognitive complexity, skills integration, and cultural relevance, and cover listening, speaking, reading, and writing, with clear, measurable rubrics. Implementation requires a paradigm shift from discrete-point testing toward an integrative assessment oriented toward the development of communicative competence. This instrument is expected to become a practical alternative for Arabic teachers to conduct more comprehensive and meaningful assessments in the Madrasah Aliyah context.